Nanocomposite formulations for enhanced oil recovery (EOR) - Rezk, Marwan Yasser (AUC Knowledge Fountain, 2017)
The energy crisis faced in the past few years by the decreasing oil prices and the restriction of recovering oil by conventional methods has developed a huge barrier. This barrier is the difficulty to recover oil by unconventional methods because of their high operation cost and the high cost of the materials required to achieve a successful operation. The main scope of this work is to investigate several zinc oxide nanocomposite formulations and their effect on enhancing oil recovery by surfactant polymer flooding methods compared to conventional surfactant polymer flooding. Since the investigation showed a good impact of ZnO nanomaterial on natural polymers but not the same on synthetic polymers and due to limited resources and time; it was decided to work on ZnO NPs/surfactant (Zinc Oxide Nanoparticles/ Surfactant) flooding instead during the core flooding phase. The work in this thesis is divided into three main phases; synthesis and characterization of nanomaterials, chemicals testing (including surfactants and polymers), and core flooding application. It was possible to fabricate reproduciable ZnO and TiO2 nanostructures. Upon characterization, preferential ZnO nanostructures were selected to undergo further testing. In the second phase, natural and synthetic polymers were tested to evaluate the impact of ZnO on their degradation and viscoelastic properties. The results showed a positive impact on natural polymers but a negative one on synthetic polymers. In addition, since the ZnO nanoparticles is flooded in the form of suspension; it was crucial to test ZnO suspension stability in various surfactants as well as the effect of ZnO NPs on interfacial tension. The results showed that ZnO NPs/SDS (Zinc oxide nanoparticles/ Sodium Dodecyl Sulphate) is the most stable suspension at ZnO concentration of 0.05 weight percent giving the most optimum reduced interfacial tension. Finally, upon the excution of core flooding experiments, the results showed an incremental oil recovery of 8% compared to conventional surfactant flooding.